Identification of Sex-Specific Markers Through 2b-RAD Sequencing in the Sea Urchin (Mesocentrotus nudus) - Cui, Zhouping; Zhang, Jian; Sun, Zhihui; Liu, Bingzheng; Zhao, Chong; Chang, Yaqing (Frontiers in Genetics, 2021)
Sex-specific markers play an important role in revealing sex-determination mechanism. Sea urchin (Mesocentrotus nudus) is an economically important mariculture species in several Asian countries and for people, its gonads are the sole edible parts. However, growth rate and immunocompetence differ by sex in this species, sex-specific markers have not been identified, and the sex-determination mechanism of sea urchin remains undetermined. In this study, type IIB endonuclease restriction-site associated DNA sequencing (2b-RAD-seq) and a genome survey of M. nudus were performed, and three female-specific markers and three female heterogametic single nucleotide polymorphism (SNP) loci were identified. We validated these sex-specific markers via PCR amplification in a large number of individuals, including wild and artificially bred populations. Several open reading frames were predicted, although there are no potential genes known for sex determination and sex differentiation within the scaffold in which the sex-specific markers are located. Importantly, the female-specific sequences and female heterozygous SNP loci indicate that a female heterogametic and male homogametic ZW/ZZ sex-determination system should exist in M. nudus. The results provide a solid basis for revealing the sex-determination mechanism of this species, and open up new possibilities for developing sex-control breeding in sea urchin.